Aktivitas Antiulseratif Berbagai Tanaman Herbal dan Prospek Masa Depan Sebagai Tanaman Budidaya : Anti-ulceritis Activity of Various Herbal Plants and Future Prospects as Cultivated Plants - Hafizh Zahra; Rosa Berlina Haridas; Gusnia Meilin Gholam; Aprijal Ghiyas Setiawan (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
Peptic ulcer disease (PUD) is one of the most common gastrointestinal disorders in individuals aged 20-50 with 1081 cases of death (0.08%) in Indonesia. The main risk factors for PUD include the use of non-steroidal anti-inflammatory drugs, Helicobacter pylori infection, alcohol, smoking, and physical stress. Nowadays, PUD treatment has transformed using secondary metabolites of herbal plants to compete with allopathic treatment adverse effects. Through this systemic review, several herbal plant metabolites from various studies are responsible for gastroprotective, inhibition of certain neurotransmitters, proton pump repression, or different anti-inflammatory effects. The literature search was carried through extensive databases (PubMed, Science Direct, Semantic Scholar, Springer Link, SAGE, and Google Scholar) with keywords linked with PUD. The scope of the data investigated included plant species, groups of metabolites, in vivo application doses, metabolites mechanism of action, and analytical methods.